Through-thickness patterns of shear strain evolve in early osteoarthritis. Issue 9 (September 2019) - Maier, F.; Lewis, C.G.; Pierce, D.M.
Summary: Objective: Given the structural changes associated with the progression of Osteoarthritis (OA), we hypothesized that patterns of through-thickness, large-strain shear evolve with early-stage OA. We therefore aimed to determine whether and how patterns of shear strains change during early-stage OA to 1) gain insight into the progression of OA by quantifying changes in local deformations; 2) gauge the potential of patterns in shear strain to serve as image-based biomarkers of early-stage OA; and 3) provide high-resolution, through-thickness data for proposing, fitting, and validating constitutive models for cartilage. Design: We completed displacement-driven, large-strain shear tests (5, 10, 15%) on 44 specimens of variably advanced osteoarthritic human articular cartilage as determined by both Osteoarthritis Research Society International (OARSI) grade and PLM-CO score. We recorded the through-thickness deformations with a stereo-camera system and processed these data using digital image correlation (DIC) to determine full-thickness patterns of strains and relative zonal recruitments, i.e., the average shear strain in a through-thickness zone weighted by its relative thickness and normalized by the applied strain. Results: We observed three general shapes for the curves of averaged through-thickness, Green–Lagrange shear strains during progression of OA. We also observed that during the progression of OA only the deep zone is recruited differently under shear in a statistically significant way. Conclusions: We propose that changes in through-thickness patterns of shear strain could provide sensitive biomarkers for early clinical detection of OA. The relative zonal recruitment of the deep zone decreases with progressing OA (OARSI grade) and microstructural remodeling (PLM-CO score), which do not consistently affect recruitment of the superficial and middle zones.